Culture shock : a handbook for 21st century business - McInnes, Will (John Wiley, 2012)
'Will McInnes has nailed it. Inspiring and comprehensive, Culture Shock is aspirational future thinking with its feet firmly on the ground'Jemima Kiss, Digital Media correspondent, The Guardian Join the work-place revolution There's a revolution afoot . . . don't be left behind. A new dawn has broken. Business has changed profoundly-fueled by aggressively advancing technology and a volatile global economy. So why has most business culture remained unchanged? Most organiz.